Trace organic compounds in oxalate rock accretions from the Lower Pecos Canyonlands of southwestern Texas. Issue 2 (4th November 2022) - Ginsberg, Sarah A.; Rayburn, Logan P.; Bray, Asya J.; Nuñuz‐Parker, Francisco S.; Dowling, Amelia; Russ, Jon
Abstract: Calcium oxalate‐rich rock coatings occur worldwide and commonly occur associated with prehistoric rock paintings. Radiocarbon dates of oxalates that cover or encapsulate rock paints have become the primary strategy for establishing chronologies of these artifacts. It is also apparent that oxalate films form episodically and are governed by particular climate conditions and thus could serve as a paleoclimate proxy. However, the mechanism(s) by which these coatings form remains unresolved. Here, we report on the trace organic composition of oxalate‐coating samples from the Lower Pecos Canyonlands in southwestern Texas. The samples contained a suite of dicarboxylic acids that are similar to the organic composition established for atmospheric aerosols. The predominant organic species in aerosols is oxalic acid, which reacts with calcium to form calcium oxalate. This suggests that aerosols could be a mechanism for the production of naturally occurring calcium oxalate on rock surfaces.